Faktor-Faktor yang Memengaruhi Siklus Menstruasi pada Remaja Putri di MAN 1 Kota Semarang - Yoelanda Anestasya Putri Widodo; Apriliani Yulianti Wuriningsih; Hernandia Distinarista (Pusat Riset dan Inovasi Nasional, 2025)
Background: Menstrual disorders that are often found in women include late menstruation, and the amount of menstrual blood. Almost 75% of adolescents experience menstruation, including irregular cycles, pain, long and heavy bleeding during menstruation. The menstrual cycle is not only influenced by biological factors such as lifestyle, hormonal disorders, nutritional status, but can also be influenced by social and environmental factors. The purpose of this study was to determine the factors that influence the menstrual cycle in adolescent girls at MAN 1 Semarang City. Method: This type of research is quantitative with a cross-sectional approach. The sample of this study amounted to 168 respondents. The respondent selection used probability sampling technique. This study used univariate, bivariate, and multivariate analysis tests. The analysis used was Spearman's rho and multiple logistic regression. Results and Conclusions: The results of this study indicate that the factors age, menarche, diet, nutritional status, and hemoglobin levels have no relationship to the menstrual cycle in female adolescents, but from the factors of stress, physical activity, fast food consumption habits, and sleep quality there is a relationship to the menstrual cycle in female adolescents at MAN 1 Semarang City where for stress level obtained p value: 0.002, physical activity with p value: 0.012, fast food consumption habits with p value: 0.035, and sleep quality with p value: 0.022. The factors that most influence the menstrual cycle in female adolescents at AN 1 Semarang City are stress levels with p value 0.002 and Od Ratio 3.365.